Oxygen uptake and respiratory exchange ratio relative to the lactate threshold running in well-trained distance runners - Tanji, F.; Nabekura, Y. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study compared oxygen uptake (VO2) and the respiratory exchange ratio (RER) between well-trained distance runners (DRs) and recreational runners (RRs) below, at, and above the lactate threshold (LT) during a four-minute run and clarified whether these variables reached steady state in DRs. METHODS: Ten male well-trained DRs (maximal oxygen uptake [VO2max], 66.8±5.9 mL/kg/min; LT, 80.0±4.4% VO2max) and nine male RRs (VO2max, 53.9±3.7 mL/kg/min; LT, 76.6±8.0% VO2max) participated in this study. They performed four-minute runs at 70%, 80%, and 90% VO2max on a treadmill. RESULTS: The results illustrated that VO2 was higher in the fourth minute than in the third minute in RRs at 80% and 90% VO2max (Cohen`s d=0.25 and 0.26, respectively), whereas, VO2 did not differ between the third and fourth minute in DRs at any intensity (Cohen`s d=0.08, 0.03, and 0.04, respectively). The RER at each intensity differed between the third and fourth minutes in RRs (Cohen`s d=0.25, 0.21, and 0.41, respectively); similarly, RER was only different between the third and fourth minutes at 90%VO2max (Cohen`s d=0.39) in DRs. CONCLUSIONS: These results indicate that the slow component of VO2 is not observed in runners with good aerobic capacity even at running intensity exceeding the LT, whereas the RER does not reach steady state at this intensity.